Prescribing indicators and pattern of use of antibiotics among medical outpatients in a teaching hospital of Central Nepal - Kumar, Jeetendra; Shaik, MM; Kathi, MC; Deka, A; Gambhir, SS (Journal of College of Medical Sciences-Nepal, 2010)
The study of prescriptions using prescribing indicators enables us to detect some common problems of prescribing and to focus subsequent efforts to correct them. This study was designed to define the extent and pattern of drug prescribing with emphasis on that of antibiotics among medical outpatients of teaching hospital of College of Medical Sciences Bharatpur, Nepal. The data contained on randomly selected original prescriptions of patients attending medical OPD in between January2008 and June2008 were collected prospectively on duplex prescriptions and analyzed. A total of 955 drugs were prescribed to 339 patients. The average number of drugs per encounter was 2.81. Drugs prescribed by generic name were 20.31% and those matched to national essential drugs list were 49.63%. Encounters with antibiotics were 43.95%. Antibiotics were the most frequently prescribed therapeutic class. Azithromycin, ciprofloxacin and amoxycillin were three most frequently prescribed antibiotics. Respiratory tract infection was the most common indication, for which antibiotics were given. Selections of antibiotics were rational for most of the indications but bacteriological confirmation prior to institution of antibiotics were not done in any case. Polypharmacy, inclination for branded products and overuse of antibiotics were revealed as problems requiring educational interventions and strict antibiotic policy as subsequent efforts to rectify them. Key words: Antibiotics; medical outpatients; prescribing indicators; teaching hospital. DOI: 10.3126/jcmsn.v6i2.3610 Journal of college of Medical Sciences-Nepal, 2010, Vol.6, No-2, 7-13